Efficacy of cypermethrin, deltamethrin and nimbicidine on fecundity and egg viability of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) (University Journal of Zoology, Rajshahi University, 2012)
Fecundity and egg viability of Tribolium castaneum (Herbst) females were significantly (P